Extension of in vivo half-life of biologically active molecules by XTEN protein polymers - Podust, Vladimir N.; Balan, Sibu; Sim, Bee-Cheng; Coyle, Michael P.; Ernst, Ulrich; Peters, Robert T.; Schellenberger, Volker (Journal of controlled release, 2016)
XTEN™ is a class of unstructured hydrophilic, biodegradable protein polymers designed to increase the half-lives of therapeutic peptides and proteins. XTEN polymers and XTEN fusion proteins are typically expressed in Escherichia coli and purified by conventional protein chromatography as monodisperse polypeptides of exact length and sequence. Unstructured XTEN polypeptides have hydrodynamic volumes significantly larger than typical globular proteins of similar mass, thus imparting a bulking effect to the therapeutic payloads attached to them. Since their invention, XTEN polypeptides have been utilized to extend the half-lives of a variety of peptide- and protein-based therapeutics. Multiple clinical and preclinical studies and related drug discovery and development efforts are in progress. This review details the most current understanding of physicochemical properties and biological behavior of XTEN and XTENylated molecules. Additionally, the development path and status of several advanced drug discovery and development efforts are highlighted. [Display omitted]